Assessment of Burnout and Job Satisfaction among Nurses Working in High-Stress Units of Tertiary Hospitals of Bahawalpur - Majeed , Rida; Fatima, Aliza; Andleeb , Hira; Fatima, Arooba; Danish, Muhammad; Ahmad , Zaeem; Jamal , Farrukh (Indus Journal of Bioscience Research, 2025)
Background: Burnout among nurses in high-stress health care settings is a growing concern worldwide, significantly impacting both staff well-being and patient care. This study aimed to assess the levels of burnout and job satisfaction among nurses working in high-stress units of tertiary hospitals in Bahawalpur, Pakistan, and to identify key contributing factors. Methods: A descriptive cross-sectional survey was conducted among 75 registered nurses working in high-stress units including General Ward, Emergency, ICU, and Operation Theatre of tertiary care hospitals in Bahawalpur, Punjab, Pakistan. Data were collected from December 06, 2024 to February 05, 2025 using a structured, closed-ended questionnaire and analyzed using IBM SPSS version 27.0.1. Key variables included demographic information (age, gender, qualification, marital status), job characteristics (work unit, shift type, experience), burnout indicators, and job satisfaction components (salary, work environment, professional growth, and coworker relationships). Statistical tests such as independent samples t-test, ANOVA, chi-square analysis, and multiple regression were applied to determine associations and predictors of burnout. Results: A total of 75 nurses participated in the study, with the majority being female (81.3%) and single (80%). Most held a BSN (45.3%) or Post-RN diploma (40%) and worked in the General Ward (62.7%), followed by Emergency (16%), ICU (12%), and OT (9.3%). Rotating shifts were the most common (52.1%). Burnout levels were moderate to high, with 69.3% sometimes feeling emotionally drained, 54.7% often tired before starting work, and 50.7% sometimes feeling burned out by the end of the shift. Additionally, 54.7% had considered leaving their job due to burnout, while 68% reported that inadequate staffing negatively affected their mental health. Job dissatisfaction was noted in salary (53.3%), work environment (40%), and career growth (45.3%), although 62.7% were satisfied with coworker relationships. Statistical analysis showed no significant differences in burnout based on gender or working unit, but a significant relationship was found between shift type and burnout. Multiple regression indicated that while age, gender, shift, and experience together did not predict burnout significantly, greater work experience was individually associated with lower burnout (β = -0.278, p = 0.046). Conclusion: High levels of emotional exhaustion and moderate job satisfaction were observed among nurses in high-stress units. Shift patterns significantly influenced burnout, while experience mitigated it. These findings highlight the need for systemic interventions, including improved shift scheduling, emotional resilience training, and institutional support systems. By addressing organizational stressors, hospitals can foster a healthier work environment and reduce nurse burnout.